1985
DOI: 10.1152/ajpheart.1985.248.1.h69
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory effects of splanchnic nerve stimulation in developing swine

Abstract: The relative maturity of immediate intestinal circulatory responses to efferent splanchnic nerve stimulation for 20 s was tested in 34 piglets (1 day-1 mo old) under pentobarbital anesthesia (15-30 mg/kg). Aortic pressure, heart rate, and superior mesenteric arterial flow (measured by electromagnetic flow transducers) were recorded simultaneously. Intestinal vascular resistance was calculated as mean aortic pressure/mean arterial flow. Resistance increased in most animals during experimental inhibition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…However, this stimulus should also have been effective in the youn ger animals because their intestinal circula tions participate in the same reflexes [9], Our effort to provide additional information on this question through the use of ganglionic blockade with hexaméthonium was limited by the subsequent hypotension that brought the intestinal perfusion pressure below the autoregulatory range in some animals and narrowed the range in others.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this stimulus should also have been effective in the youn ger animals because their intestinal circula tions participate in the same reflexes [9], Our effort to provide additional information on this question through the use of ganglionic blockade with hexaméthonium was limited by the subsequent hypotension that brought the intestinal perfusion pressure below the autoregulatory range in some animals and narrowed the range in others.…”
Section: Discussionmentioning
confidence: 99%
“…Although pentobarbital is known to depress the heart and ele vate aortic pressure (AoP) in swine [ 1. 18,24], we have shown that the baroreceptor reflexes [4,9] and periph eral vascular constrictor responses [5. 8.…”
Section: General Proceduresmentioning
confidence: 99%
See 3 more Smart Citations